Romanian Banking System: The Degree of Financial Intermediation After the Financial Crisis - Mihaita-Cosmin Popovici (CES Working Papers, 2014)
In this paper we analyze the evolution of the Romanian banking system after the 2007 financial crisis and the country's accession to the European Union. The first part analyzes the main elements of the banking system: ownership structure, number of employees and banking units, loans and non-performing loans. The second part analyzes the level of financial intermediation of the banking system. The results showed that majority of the capital is private and foreign, the top five banks held over half of the bank assets, number of employees decreased due to the crisis and non-performing loans share had increased by over nine times. Romanian banking system have a low degree of financial intermediation, but the new developments of the EU banking systems proved that it can be a strong point.
Keywords: G01; G21; 330; Romania; banking system; degree; financial intermediation